Research, innovation and technological performance in Germany - EFI Report 2012 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2012)
In their Annual Report 2012, the Commission of Experts for Research and Innovation once again addresses current developments in Germany and presents detailed analyses of core topics relating to research and innovation policies. Although Germany fell short of the three-percent target, the country's research and development (R&D) intensity has systematically increased over the last years. Yet, in the long term, the Federal Government should aim at thinking beyond the three-percent target. For the year 2020, it should strive for more ambitious goals than it has previously. On a European scale, a considerable gap in productivity can be observed. The present crisis of the European Union (EU) provides a perfect illustration of this fact. In collaboration with its European partners, the Federal Government should be committed to strengthen the innovative power of the entire European region. At the same time, the attractiveness of Germany as an R&D location should be further improved. R&D tax credits are, and will continue to be, a useful measure for achieving this. The Energy Transition that was launched by the Federal Government in the early summer of 2011 poses new challenges to Germany, but it also offers interesting economic perspectives. Yet, at this point in time the Expert Commission can only see reserved reactions within the German research system.
Keywords: 330